Le Savon Sdn. Bhd. / Nayli Ulfah Muhd Nasruddin - Muhd Nasruddin, Nayli Ulfah (2020)
Le Savon Sdn. Bhd. is one of the new and rising companies in Malaysia. The company is focused on building products and exceptional services needed by their customers. Le Savon is headquartered in Shah Alam, Selangor and was founded by Nayli Ulfah. Le Savon launched its first product in 2020. Since then, Le Savon has grown exponentially in terms of products and services. Today, one of the most successful products of Le Savon is the automatic soap dispenser. It is an automatic soap dispenser which dispense a controlled amount of soap solution or any similar liquid. They function to conserve the amount of soap used and stop infectious disease transmission. The biggest and most important advantage of an automatic soap dispenser compared to a regular one is the fact that it can be used without touching it. That eliminates a contact point and means fewer bacteria and a cleaner surface for a longer time.